Ozone isotopologue measurements from the Atmospheric Chemistry Experiment (ACE). (November 2019) - Fernando, Anton M.; Bernath, Peter F.; Boone, Christopher D.
Highlights: Global isotopologue fractionations of ozone measured by the ACE satellite mission. A high-resolution Fourier transform spectrometer is used in solar occultation method. Heavy isotopologues are enriched in tropical stratosphere and in the upper stratosphere of the Antarctic polar vortex. Abstract: Near global ozone isotopologue distributions have been determined from infrared solar occultation measurements of the Atmospheric Chemistry Experiment (ACE) satellite mission. ACE measurements are made with a high resolution Fourier transform spectrometer. Annual and seasonal latitudinal fractionation ( δ value) distributions of the ozone isotopologues 16 O 16 O 18 O, 16 O 18 O 16 O and 16 O 17 O 16 O were obtained. Asymmetric ozone ( 16 O 16 O 18 O) shows higher fractionation compared to symmetric ozone ( 16 O 18 O 16 O). The maximum ozone fractionation occurs in the tropical stratosphere as expected from the contribution of photolysis to the enrichment of heavy isotopologues. An enhancement of the heavy ozone isotopologues is also seen in the upper stratosphere of the Antarctic polar vortex.